PTH-102 Renal dysfunction is an early morbid event in intestinal transplantation. (23rd September 2015) - Sivaprakasam, R; Wiles, A; Woodward, J; Duncan, S; Tincknell, H; Watson, C; Butler, A; Gabe, S; Praseedom, R; Jamieson, N N V; Middleton, S J
Abstract : Introduction: Renal dysfunction (RD) following intestinal transplantation (SBTx) contributes to significant morbidity and is associated with reduced patient survival. RD has been shown to occur within the first two postoperative years, but renal function in the early postoperative period is poorly described. Methods: The study was performed in a single centre on patients who had a minimum survival of 6 months following small bowel/multivisceral transplantation. A total of 20 transplants were performed during the study period and 11 were eligible for this study. The data collected were recipient demographics, pre-transplant renal function, donor demographics, immunosuppressive therapy. Renal function (measured by serum creatinine and e-GFR), serum Tacrolimus levels were at 7, 14 and 21 days, 6, 12, 18 and 24 months and 3 years. In addition, number of admissions, acute rejection episodes, need for modulation of immunosuppressants and function of the allografts. The data were retrieved from a prospectively collected database. Results: 8/11 patients had deterioration in the renal function with mean serum creatinines at Day 14, 21 of 172.4 and 161.2 μmol and at 3 and 6 months 163.1 and 143.9 μmol, respectively. The serum Tacrolimus levels were well controlled between 8.27 and 9.17 μg/l throughout the study period. The RD was treated by 3/8 patients being converted to m-TOR inhibitors and in the other 5/8 patients reduced Tacrolimus levels were used. The renal function for patients converted to MTOR inhibitors improved. The mean number of admissions in the first year after the transplant was 3.66 and 4.13 during 3 years. There was an association between the number of readmissions and renal dysfunction suggesting that these patients had a poorer outcome as previously observed by others. However, we did not find an association between RD and Tacrolimus levels which other have reported. Conclusion: In our cohort, the renal dysfunction was noted in 73% (8/11) of patients and it occured within the first month of the SBTx. The association with readmission suggests it is related to impaired outcome, its cause remains speculative.